Correlation of X-Ray Diffraction, X-Ray Absorption Spectroscopy and Optical Properties of Europium Activated Spaniel Calcium Stannate. Issue 1 (4th May 2022) - Padchasri, Jintara; Tipakontitikul, Rungnapa; Niyompan, Anusorn; Sattayaporn, Suchinda; Chanlek, Narong; Kidkhunthod, Pinit; Rujirawat, Saroj; Yimnirun, Rattikorn; Manyum, Prapun
Abstract: Ca2 SnO4 :xEu 3+ phosphors were synthesized by solid-state reaction method and characterized systematically using by XRD, XANES, EXAFS and PL spectroscopy. The XRD, XANES and EXAFS confirmed the formation of the Ca2 SnO4 and the stabilization of Sn and Eu ions in 4+ and 3+ oxidation states. The PL properties of theses phosphor were investigated at room temperature. The emission spectra represent reddish-orange performance, which is due to the 5 D0 → 7 FJ ( J  = 0, 1, 2, 3, 4) transition of Eu ions. The red emission from transition 5 D0 → 7 F2 (red) is dominate over that of 5 D0 → 7 F1 (orange). The impact of doping Eu 3+ and PL properties were investigated, and we propose a feasible interpretation, which this phosphor could be a good candidate as a reddish-orange component in the fabrication of white LEDs.